Teacher and Student Talk in Learning Speaking Skill at SMA Bina Bersaudara Medan - Fathul Jannah Harahap; Indra Hartoyo (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
This study aimed (1) to investigate the types of teacher and student talk in English classroom interaction and (2) to investigate the teacher and students’ reasons to use the types of categories in classroom interaction. This study focuses on analyzing the process of classroom interaction through Flanders Interaction Analysis Categories System (FIACS). This study was conducted by using descriptive qualitative research. It was conducted in SMA Bina Bersaudara Medan at the X-1 grade class. The instruments of the research were observation, recording and interview. The results of this study were (1) the types of teacher talk that occurred were praise or encourages, asking question, lecturing and giving direction. Furthermore, the types of student talk that occurred were response and silence or confusion. (2) There are four reasons why the teacher used the types of categories in classroom interaction, namely: the teacher used praise and encourage to make students feel appreciated, the teacher used asking question because the teacher want to improve students’ skill and to make students understood about the topic being discussed before getting into the next topic, the teacher used lecturing to make process of teaching and learning in the classroom to be successful, the teacher used giving direction because teacher wanted to know whether the students have understood about the material or not. There are two reasons why students used the types of categories in classroom interaction, namely: students respond to the teacher because they understood about the topic being discussed, the students wanted to try their ability and to know the extent of their knowledge about the topic, the students silence or confusion when the teacher asked question because the students didn’t understand the question given by the teacher, according to them the lesson is very difficult to understood, and they didn’t understand the topic being discussed.Keywords: Teacher Talk, Student Talk, Flanders Interaction Analysis Categories System (FIACS).